Pengaruh Behavioral Factors Terhadap Keputusan Investasi Saham Di Indonesia - Ananda Athoillah; Yuyun Isbanah (PT. Inovasi Teknologi Komputer, 2024)
This study was conducted with the aim of determining whether or not there is an influence of behavioral factors on investment decisions in the Indonesian stock market. This research is a quantitative research with a causality approach. The population in this study is investors registered in KSEI with a sample of 400 respondents taken using purposive sampling technique. The data used are primary data collected through the distribution of questionnaires. The data that has been collected is then processed and analyzed using multiple linear regression. The results showed that the overconfidence variable affects the choice of investing in Indonesia. Investor sentiment variables partially have an impact on investment decisions according to Planned Behavior Theory, where someone invests based on subjective norms. In this study, the herding behavior variable had a considerable positive impact on stock investment decisions in Indonesia.